Diseño textil para acolchados aplicando rellenos con materiales alternativos - Robalino Ruiz, Emily Marcela (2024)
The proposed integrative project aims to explore new alternatives to replace down in quilts by using sustainable and efficient alternative materials. Through comprehensive research, the feasibility of various materials available in the market for their application in textile quilts will be evaluated, considering their physical, chemical, and mechanical properties. Experimentation will be conducted to develop aesthetically appealing and functional quilted textile designs without compromising quality or comfort. Additionally, a textile catalog will be created to showcase the designs, highlighting their diversity and sustainability through a rigorous process of research and experimentation, with appropriate surface treatments to emphasize details and quality. These results are expected to contribute to the advancement of textile design and quilt production, promoting more sustainable practices in the industry and offering innovative alternatives that meet market needs, thus driving economic and social development in the textile sector, in line with current trends towards sustainability and innovation in textile design. This project is carried out with the objective of researching and developing quilted textile designs that use alternative materials as fillings, replacing down, with the fundamental purpose of exploring new options that are sustainable and efficient, thereby contributing to advancements in the field of textile design and quilt production.